PAIN IN NEONATES: PREVALENCE, DIAGNOSTICS, PREVENTION AND TREATMENT - Y. V. Zhirkova; Y. I. Kucherov; S. M. Stepanenko (Педиатрическая фармакология)
Pain in neonates is often ignored by medical staff, it remains undetected and without adequate treatment. The increased interest in recent years to the problem of pain control in the neonates period is determined by early and long-term adverse effects on the child. The article highlights the features of the perception of pain in newborns including premature infants, examines the pain epidemiology, methods of diagnosis, its prevention and treatment. Considering the difficulty in determining the pain in this age group, the attention is emphasized on the leading role of medical staff in the pain control in newborns.